Redox Changes Induced by General Anesthesia in Critically Ill Patients with Multiple Traumas - Papurica, Marius (Mol Biol Int, 2015)
The critically ill polytrauma patient is a constant challenge for the trauma team due to the complexity of the complications presented. Intense inflammatory response and infections, as well as multiple organ dysfunctions, significantly increase the rate of morbidity and mortality in these patients. Moreover, due to the physiological and biochemical imbalances present in this type of patients, the bioproduction of free radicals is significantly accelerated, thus installing the oxidative stress. In the therapeutic management of such patients, multiple surgical interventions are required and therefore they are being subjected to repeated general anesthesia. In this paper, we want to present the pathophysiological implications of oxidative stress in critically ill patients with multiple traumas and the implications of general anesthesia on the redox mechanisms of the cell. We also want to summarize the antioxidant treatments able to reduce the intensity of oxidative stress by modulating the biochemical activity of some cellular mechanisms.